Whole genome sequencing for drug-resistant tuberculosis management in South Africa: What gaps would this address and what are the challenges to implementation?. (August 2019) - Dlamini, Mlungisi Thabiso; Lessells, Richard; Iketleng, Thato; de Oliveira, Tulio
Abstract: Global control of tuberculosis (TB) has been seriously impacted by the emergence and transmission of its drug-resistant forms. Delayed detection and incomplete characterisation of drug-resistant tuberculosis (DR-TB) contributes to morbidity and mortality, and to ongoing transmission of drug-resistant strains. Current culture-based and molecular diagnostic tools for TB present numerous disadvantages that could potentially lead to misdiagnosis, inappropriate treatment initiation and the amplification of drug resistance. The detection of drug-resistant tuberculosis (DR-TB) in South Africa relies on molecular diagnostic assays such as the Xpert MTB/RIF and line probe assays (MTBDR plus and MTBDR sl ). However, these molecular assays are limited to detecting resistance to only a few first-line and second-line drugs. It is for this reason that next-generation sequencing (NGS) and bioinformatics pipelines have been developed for rapid detection of M. tuberculosis drug resistance, with the added advantage that sequence data could also have public health applications through understanding transmission patterns. This review highlights some of the challenges that are currently hampering the diagnosis and control of DR-TB in a high burden setting of the KwaZulu-Natal (KZN) province in South Africa. Shortfalls of current diagnostic techniques for DR-TB are discussed in detail and we also propose how these might be overcome with an accurate and rapid NGS system.